2009
DOI: 10.4161/chan.3.4.9254
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular potassium dependency of block of HERG by quinidine and cisapride is primarily determined by the permeant ion and not by inactivation.

Abstract: Drug induced Long QT syndrome results primarily from block of the cardiac potassium channel heRG (human-ether-a-gogo related gene). In some cases prolongation of the QT interval can result in the lethal arrhythmia torsade de pointes, an arrhythmia characterized by a rapid heart rate and severely compromised cardiac output. Many patients requiring medication present with abnormal serum electrolyte levels due to a variety of conditions including gastrointestinal dysfunction, renal and endocrine disorders, diuret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…A number of reports have suggested that block of HERG by some drugs is sensitive to extracellular potassium 8,10,11,20,27 whereas block of HERG by other drugs is not sensitive to extracellular potassium. 12,13,28 In particular block of HERG by dofetilide has been shown to be independent of extracellular potassium over a concentration range from 2 mM to 50 mM.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of reports have suggested that block of HERG by some drugs is sensitive to extracellular potassium 8,10,11,20,27 whereas block of HERG by other drugs is not sensitive to extracellular potassium. 12,13,28 In particular block of HERG by dofetilide has been shown to be independent of extracellular potassium over a concentration range from 2 mM to 50 mM.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that block of HERG by a number of different drugs, including quinidine and cisapride is reduced with an increase in extracellular potassium. 8,10,11 However additional studies have shown that block of by two other drugs, quinidine and cisapride, is reduced with an increase in extracellular potassium. 10 Both bepridil and terfenadine are trapped inside the channel after channel closure, whereas quinidine and cisapride cannot be trapped inside the channel after the channel closes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations